Sifat Mekanik API 5l X-65 Cladded UNS N08825 Akibat Pengaruh Perbaikan Las - Defi Pramesti; Winarto, Winarto (Jurnal Mesin Nusantara, 2023)
Abstract This study evaluate the mechanical characteristics and microstructure of API 5L X-65-clad UNS N08825 during repair welding. Gas tungsten arc welding (GTAW) and shielded metal arc welding were used in combination to carry out the welding and the repair welding (SMAW). Filler metals ER NiCrMo3 and E NiCrMo3 were used throughout the GTAW and SMAW welding processes. The first specimen served as the primary focus, after which the weld areas of the remaining four specimens were ground, re-beveled, and then re-welded using the same parameters. It performed tensile testing, bending tests, Impact Charpy tests, macro photography tests, and Vickers hardness tests. Repairs weld carried out, the heat-affected zone's hardness in the capping region increased. The findings of the tensile test demonstrate that the tensile strength is not considerably impacted by the welding repair at any particular welding repair location. The biggest decline in the number is caused by the welding repair at PTR 2, which is 0.83 percent. The heat affected area (FL) value decreased by 10.44 percent according to the charpy impact test results. The PTR 1 and PTR 2 areas in the weld metal area had the lowest charpy impact test results, respectively, of 88 J and 258 J.